Exploration of anti-stress mechanisms in high temperature exposed juvenile golden cuttlefish (Sepia esculenta) based on transcriptome profiling - Wang, Yongjie; Bao, Xiaokai; Wang, Weijun; Xu, Xiaohui; Liu, Xiumei; Li, Zan; Yang, Jianmin; Yuan, Tingzhu (Frontiers in Physiology, 2023)
With the acceleration of industrialization in recent years, the sharp rise in CO2 emissions has induced global warming and an increased sea temperature, which will seriously affect the growth and development of organisms and other physiological activities. Sepia esculenta is a cephalopod widely distributed in the Western Pacific Ocean. Due to its high economic and nutritional value, research on it has gradually increased in recent years. The low anti-stress ability of larvae makes it difficult to adapt to high ambient temperature. High ambient temperature will make the larvae produce intense stress responses, affecting survival, metabolism, immunity, and other life activities. The molecular mechanisms by which larval cuttlefish cope with high temperatures are not well understood. In this study, we performed transcriptome sequencing of S. esculenta larvae and identified 1,927 differentially expressed genes (DEGs). DEGs were used to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses. The top 20 terms of biological processes in GO and 20 high-temperature stress-related pathways in KEGG functional enrichment analysis were identified. A protein-protein interaction network was constructed to study the interaction between temperature stress-related genes. And 30 key genes with high number of KEGG signaling pathways participants or number of protein-protein interactions were identified and verified by quantitative RT-PCR. We explored the functions of three hub genes including HSP90AA1, PSMD6, and PSMA5, the heat shock protein family, and proteasome through the comprehensive analysis of protein-protein interaction network and KEGG signaling pathway. Our results are helpful to further understand the mechanism of high temperature resistance in invertebrates and provide more reference for the S. esculenta industry in the context of global warming.